Pengembangan Muatan Kecakapan Hidup (Life Skill) pada Pembelajaran di Sekolah - Nindya Yuliwulandana (Tarbawiyah Jurnal Ilmiah Pendidikan, 2015)
Life skill education is education that provides a set of beneficial skills/capabilities to the learners in order they can be self-sufficient in their community. Life skill education provides many benefits and it gives an impact of economic improvements for the community. It will also give them more benefits to improve their better life with some indicators: social welfare increasing, reduction of destructive behavior that can reduce social problems, and development of society in harmony which is capable in combining religious values, theory, solidarity, economy, power and art (taste). The instruction of life skills education to students will reflect the values of real life and it will build an effort to fulfill the demands of real life. Most of Learners live in a social environment that upholds the values of togetherness; therefore they should have the ability to lead and to be led which are supported by the spirit of entrepreneurship. The drop out students will not also face many problems of life because they have had the life skills for their future. Life skills education can be implemented through a variety of ways. It is adapted for the context of schools and learners. The application of life skills education can be integrated by learning for each subject through the local content subjects or self-development.